Subicular hypotrophy in fetuses with Down syndrome and in the Ts65Dn model of Down syndrome. (15th November 2018) - Stagni, Fiorenza; Giacomini, Andrea; Emili, Marco; Uguagliati, Beatrice; Bonasoni, Maria Paola; Bartesaghi, Renata; Guidi, Sandra
Abstract: Intellectual disability in Down syndrome (DS) has been attributed to neurogenesis impairment during fetal brain development. Consistently with explicit memory alterations observed in children with DS, fetuses with DS exhibit neurogenesis impairment in the hippocampus, a key region involved in memory formation and consolidation. Recent evidence suggests that the subiculum plays a unique role in memory retrieval, a process that is also altered in DS. While much attention has been devoted to the hippocampus, there is a striking lack of information regarding the subiculum of individuals with DS and DS models. In order to fill this gap, in the current study, we examined the subiculum of fetuses with DS and of the Ts65Dn mouse model of DS. We found that in fetuses with DS (gestational week: 17–21), the subiculum had a reduced thickness, a reduced cell density, a reduced density of progenitor cells in the ventricular zone, a reduced percentage of neurons, and an increased percentage of astrocytes and of cells immunopositive for calretinin—a protein expressed by inhibitory interneurons. Similarly to fetuses with DS, the subiculum of neonate Ts65Dn mice was reduced in size, had a reduced number of neurons and a reduced number of proliferating cells. Results suggest that the developmental defects in the subiculum of fetuses with DS may underlie impairment in recall memory and possibly other functions played by the subiculum. The finding that the subiculum of the Ts65Dn mouse exhibits neuroanatomical defects resembling those seen in fetuses with DS further validates the use of this model for preclinical studies.